Electre Method for Determining Car Stock at PT. New Ratna Motor with a Customer Satisfaction Approach - Saifur Rohman Cholil; Henny Indriyawati (Jurusan Teknologi Informasi Universitas Semarang, 2019)
Managing car stock is the biggest challenge for a company, especially in PT. New Ratna Motor engaged in automotive. The problem is related to the process of selling goods where the sales and car stock are out of balance. Comparisons between cars entering and cars coming out (sales) are larger cars that enter so that there is a buildup of stock in the number of cars which results in company losses which include running taxes that must be paid each year, as well as the accumulation of certain types of cars and spending on car parking. The ELECTRE method is applied as a method in determining what types of cars should be stocked by the company based on customer satisfaction, if the customer is satisfied with one type / type of car and quickly gets the unit, chances are the customer will buy or reference the product. The final result of this study is the ranking of the alternatives for determining the stock of the car.